Reciprocal relationships between self-control and self-authenticity: a two-wave study - Li, Qingqing; Ren, Xiaomei; Zhou, Zongkui; Wang, Jing (Frontiers in Psychology, 2023)
Both self-control and self-authenticity are critical to individuals’ mental health and social adjustment, but their relationship has received little attention. Research demonstrates that exerting self-control could help individuals achieve true self and might be promoted by perceiving authenticity. Accordingly, this study utilized a longitudinal design and investigated the temporal relationship between self-control and self-authenticity in a large sample of 2982 Chinese adolescents (Mage = 17.53, SD = 0.84). Correlation analysis showed that participants possessing higher self-control were associated with greater self-authenticity. Cross-lagged path analysis revealed a reciprocal relationship between self-control and self-authenticity over time. Moreover, bivariate latent change score model indicated that self-control predicted an increase in self-authenticity across time, and vice versa. Overall, this study advances our understanding and suggests that restraining temptation and impulse can promote adolescents’ authenticity, and that the experience of authenticity, in turn, facilitates their self-regulation.